Husband's Role in Perinatal Depression during the New Normal Period of the Covid-19 Pandemic in Sewon Sub-District - Sylvi Wafda Nur Amelia; Christina Pernatun Kismoyo (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
The Covid-19 pandemic has greatly impacted the welfare and health of the community, which also lead to a perinatal mental health problem. Perinatal depression is not only due to hormonal fluctuations experienced by perinatal women, but also by the emotional challenges of having to keep a vulnerable newborn baby alive, while the mother gets little rest. Since a woman often lacks rest, the husband's participation in perinatal care can reduce stress on perinatal women. This study aims to determine the relationship between husband's participation and the incidence of perinatal depression during the Covid-19 pandemic. This was an observational analytical study with a cross sectional approach. The study population involved perinatal women and their husbands in Sewon Sub-District. Twenty-eight perinatal women lived in Sewon Sub-District participated in this study. The samples of 0-1month postpartum women were selected through simple random sampling technique. Data were analyzed using chi square test. The results revealed that 51.4% respondents had mild postpartum depression because their husbands participated in infant care. The chi-square value was 17,754 (higher than X2 table of 5.591) with a p-value of 0.000<0.05. Thus, Ho was rejected, meaning that there was a relationship between husband's participation in infant care and postpartum depression in Sewon Sub-District.